Methods of integrating patriotism values into tertiary English literature courses / Shi Shaohua and Revathi Gopal - Shi, Shaohua; Gopal, Revathi (Universiti Teknologi MARA, Kedah, 2024)
The patriotic function of tertiary education is becoming more and more essential as the countries and regions are communicating with each other more and more frequent in fields of economy, culture and education. In order to guarantee the stability of a country’s long-term development, the future inheritors’ patriotism consciousness can produce long-lasting and profound influence on the future development. Among all the tertiary courses, English literature plays a special and irreplaceable role in terms of cultivating cultural preference, consolidating patriotic consciousness and foster their patriotic behaviors. Because the English literature courses implements teaching through original foreign textbooks, which contain potential misleading values and too much focus on the advanced aspect will probably lead to blind worshiping and irrational affection. The following study employs the qualitative research method, a case study of the English literature classroom in a selected university in China. The study will answer two research questions. First, how do the English literature teachers teach English literature integrated with patriotism values? Second, what guidelines can be proposed to consolidate the English literature teaching and learning in terms of the basic teaching design, from teaching goal, teaching materials to assignment for students?